Anal Intraepithelial Neoplasia: Precursor of Anal Squamous Cell Carcinoma - Taku Sakamoto (Journal of the Anus, Rectum and Colon, 2022)
Anal squamous cell carcinoma (SCC) is rare, but it has been commonly detected as an invasive cancer. The standard treatment for anal SCC was surgical resection. However, recent medical advances have enabled the standard treatment to be chemoradiotherapy. Anal intraepithelial neoplasia (AIN) is a premalignant lesion of SCC. The screening test for AIN and human papilloma virus vaccine are important for the following high-risk patients: patients positive for human immunodeficiency virus and men who have sexual intercourse with men. Although cytology can be easily applied for a screening test, the false-negative rate for AIN is high. Instead, high-resolution anoscopy (HRA) has been gaining attention as a promising screening method for high-risk patients. Investigations comparing characteristic findings of HRA with the histology of AIN have demonstrated that HRA is a highly specific test for AIN. Magnifying or image-enhanced endoscopies are also routinely used for colonoscopy, as they allow detailed observations at higher magnifications than those of HRA. Hence, these endoscopic modalities can be applied for assessing AIN. Ablation therapies or topical medications are available as the local treatment for AIN. Although endoscopic submucosal dissection is considered to be feasible to remove AIN, it has a technical difficulty to approach endoscopically invisible areas. Hence, this technique may be useful to resect AIN localized in the endoscopically visible areas, when the localization is confirmed via targeted biopsy.